Optimal Conservatism and Collective Monetary Policymaking under Uncertainty - Carsten Hefeker; Blandine Zimmer (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study how the optimal degree of conservatism relates to decision-making procedures in a Monetary Policy Committee (MPC). In our framework, central bank conservatism is required to attenuate the volatility of monetary decisions generated by the presence of uncertainty about the committee members' output objective. We show how this need for conservatism varies according to the number of MPC members, the MPC's composition as well as its decision rule. Moreover, we find that extra central bank conservatism is required when there is ambiguity about the MPC's true decision rule.
Keywords: D70; E52; E58; F33; 330; monetary policy committees; central bank transparency; central bank conservatism; min-max